2015
DOI: 10.18203/2349-2902.isj20150949
|View full text |Cite
|
Sign up to set email alerts
|

Incidental carcinoma of gallbladder in north India: is routine histopathology of all cholecystectomy specimens justified?

Abstract: Background: Gallstones can cause varied spectrum of histopathology. Xanthogranulomatous cholecystitis and metaplasia have been shown to have association with carcinoma gallbladder. Incidental carcinoma of the gallbladder is a nightmare for the patient. Routine histopathology of all cholecystectomy specimens is an effective policy for its early diagnosis and management. Methods: It is a retrospective study of histopathology of cholecystectomy specimens related to gallstones disease done at a rural government in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
4
9
1
Order By: Relevance
“…The prevalence of chronic cholecystitis, the most common pathology within our patient population, was noted to be 78.7%. In accordance with this finding, a study concluded the prevalence of chronic cholecystitis to be 79.8%, which bears remarkable semblance to our finding [19]. Chronic cholecystitis is characterised by marked thickening of the GB wall with associated calcifications, eventually culminating in a pathology termed the porcelain GB.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of chronic cholecystitis, the most common pathology within our patient population, was noted to be 78.7%. In accordance with this finding, a study concluded the prevalence of chronic cholecystitis to be 79.8%, which bears remarkable semblance to our finding [19]. Chronic cholecystitis is characterised by marked thickening of the GB wall with associated calcifications, eventually culminating in a pathology termed the porcelain GB.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, cholesterolosis was observed in 32.8% of the cases. A study conducted by Mondal et al concluded the presence of the pathology in merely 2.9% of the patient population, while Sangwan et al reported a prevalence of 9.43% [5,19]. The prevalence of the pathology in our study was therefore noted to be significantly higher.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The studies that recommend routine histology following cholecystectomy state that a large number of IGBC detected are missed by the surgeons as suspicious gallbladders and are later diagnosed as a histological surprise (Jeelani et al, 2019;Jha et al, 2018;Lundgren et al, 2018;Patel et al, 2016;Sangwan et al, 2015;V et al, 2013;Ghimire et al, 2011;Haq et al, 2011;Shrestha et al, 2010;Khan et al, 2007;Samad, 2005). Routine recommending studies highlight the grave consequences of missing many GBC by not doing routine histological evaluation especially in areas with a high incidence of gall bladder cancer and also because of the bad prognosis associated with the disease (Jeelani et al, 2019;Jha et al, 2018;Patel et al, 2016;Siddiqui et al, 2013).…”
Section: Diagnosis Of Gallbladder Cancer By Routine Evaluationmentioning
confidence: 99%
“…One of the most common diseases among gastrointestinal disorders are those arising from gall bladder. The disease entity varies from cholecystitis (acute, chronic, follicular and xanthogranulomatous), cholelithiasis, cholesterolosis, adenomatous hyperplasia, metaplasia and carcinoma 1 . According to recent epidemiologic study, there is evidence of strong association of Helicobacter pylori species with chronic cholecystitis, gall bladder carcinoma and cholesterol stones.…”
Section: Introductionmentioning
confidence: 99%